Effects of vaginal microbiota transfer on the neurodevelopment and microbiome of cesarean-born infants: A blinded randomized controlled trial - Zhou, Lepeng; Qiu, Wen; Wang, Jie; Zhao, Aihua; Zhou, Chuhui; Sun, Tao; Xiong, Ziyu; Cao, Peihua; Shen, Wei; Chen, Jingfen; Lai, Xiaolu; Zhao, Liu-hong; et al. (Cell host & microbe, 2023)
The microbiomes of cesarean-born infants differ from vaginally delivered infants and are associated with increased disease risks. Vaginal microbiota transfer (VMT) to newborns may reverse C-section-related microbiome disturbances. Here, we evaluated the effect of VMT by exposing newborns to maternal vaginal fluids and assessing neurodevelopment, as well as the fecal microbiota and metabolome. Sixty-eight cesarean-delivered infants were randomly assigned a VMT or saline gauze intervention immediately after delivery in a triple-blind manner (ChiCTR2000031326). Adverse events were not significantly different between the two groups. Infant neurodevelopment, as measured by the Ages and Stages Questionnaire (ASQ-3) score at 6 months, was significantly higher with VMT than saline. VMT significantly accelerated gut microbiota maturation and regulated levels of certain fecal metabolites and metabolic functions, including carbohydrate, energy, and amino acid metabolisms, within 42 days after birth. Overall, VMT is likely safe and may partially normalize neurodevelopment and the fecal microbiome in cesarean-delivered infants. [Display omitted] •This triple-blind RCT shows that VMT may be safe for cesarean-born infants•VMT is associated with improved neurodevelopment in cesarean-born infants•VMT could restore the gut microbiome to resemble that of vaginally delivered infants•VMT regulates levels of certain gut metabolites and metabolic pathways The safety and effect of vaginal microbiota transfer (VMT) on cesarean-born infants continues to be debated. In a triple-blind randomized controlled trial, Zhou et al. show that VMT is likely safe and may partially normalize neurodevelopment and the fecal microbiome in cesarean-born infants, supporting its potential health benefits.